Application Traceability System in Fish Processing Lemadang Frozen Portion in PT. Graha Insan Sejahtera, North Jakarta - Dwi Febrianik; Niken Dharmayanti; Arpan Nasri Siregar (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2017)
Rejection of any foreign material that should not be included in the product (filthy) occurs in fish lemadang with various forms of products. The observe done in PT. Graha Insan Sejahtera, North Jakarta from 15 February until 15 May 2016. The purpose of observe was to determine the application of traceabilitysystems in the fish processing frozen lemadang portion and determine the ability of a search on the final product based on the code traceability. Method end the practice of using direct observation by participating in the process of traceability and interviews with sources (captains, tally, Quality Assurance or QA and Quality Control or QC). Implementation of traceability systems internally applied by Fish Processing Unit (UPI) based analysis system, the type of operation and methods of data traceability. Implementation of internal code traceability system starting from raw material to the acceptance stage weighing IV use 12-digit numbers and three letters or a combination of numbers and letters. At this stage of labeling up to loading using a product lot code. The application of an external traceability system on seven ships and three suppliers no implementing traceability systems. Search capability to the code portion lemadang frozen fish products with a known product quality is not traceable to get the code of raw materials and the quality of frozen fish lemadang.